Predictors of adherence to preconception and prenatal micronutrient supplementation in Vietnam - Gonzalez-Casanova, Ines; Nguyen, Phuong Hong; Harding, Kimberly B.; Reinhart, Gregory A.; Nguyen, Hieu; Truong, Truong V.; Pham, Hoa; Nguyen, Son; Martorell, Reynaldo; Ramakrishnan, Usha (Wiley, 2015)
We examined predictors of adherence to preconception and prenatal micronutrient supplementation, using data from a randomized controlled trial in rural Vietnam. 5011 women of reproductive age were randomized to receive weekly PRECONCEPT supplements containing either: Folic Acid, Iron and Folic Acid (IFA), or Multiple Micronutrients. Women who became pregnant (1744) received daily prenatal IFA (GESTCARE) supplements through delivery. Monitors visited women's homes every 14 d to deliver supplements and record consumption and side effects. 59% and 75% consumed all the tablets that they received for PRECONCEPT and GESTCARE, respectively. In logistic regression analyses, women anemic at baseline (OR, 95% CI=1.25, 1.06 1.47), farmers (OR, 95% CI=1.28, 1.07 1.53), and minority ethnicity (OR, 95% CI=1.50, 1.31 1.71) were more likely to have lower adherence to PRECONCEPT supplements and minority ethnicity with lower adherence to GESTCARE (OR, 95% CI=1.33, 1.01 1.77). There were no differences by type of supplement. Parity, body mass index, side effects, and education did not predict adherence (p>0.05). Adherence to preconception and prenatal supplementation was high among women from a rural province of Vietnam. Lower adherence in vulnerable groups suggests a need to develop tailored behavior change interventions to accompany micronutrient supplementation in this population. Funded by the Micronutrient Initiative and the Mathile Institute.